Effect of Lining Papers on the Permanence of Painting Papers in Japanese Scroll Paintings During Moist Heat Ageing. (19th May 2022) - Lee, Kang; Enomae, Toshiharu; Inaba, Masamitsu
ABSTRACT: A Japanese painting paper is sized with an aqueous solution of alum and animal glue followed by brushing with a mixture of pigments of various colours and aqueous animal glue solution. Subsequently, to mount the Japanese painting to a hanging scroll, the backside of the painting is lined with a first lining paper using wheat starch paste for mechanical support. To evaluate the permanence of the painting paper as a composite material in the hanging scroll, the deterioration behaviour of the unlined painting paper and the lined painting paper was compared considering the material dynamics. After moist heat accelerated ageing (80°C, 65% RH), in the sample immersed in a CuSO4 ・5H2 O solution, cellulose was oxidised by Cu 2+ to generate organic acids in the painting paper, and Cu 2+ and organic acids migrated to the lining paper. Consequently, the discolouration and oxidation of the painting paper in the lined complex were relatively low compared with those of the unlined painting paper. The pH decrease in the painting paper was also small in the lined complex. Moreover, if the animal glue solution was coated on the painting paper, a buffer effect was shown to operate against the organic acids derived from the oxidation of Cu 2+, thereby inhibiting the migration of Cu 2+ into the lining paper. In conclusion, the presence of the lining paper inhibited the decrease in the physical strength and degree of polymerisation of the cellulose in the painting paper, thus contributing to its permanence in the lined hanging scroll.